Analisis Faktor Yang Mempengaruhi Waktu Tunggu Kapal Di Pelabuhan Tanjung Intan Cilacap - Mawardi, Kholid; Santoso , Wahyudi; Weda , Iwan; Yulianto, Yulianto (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
The waiting time for ships is one of the problems that must be a concern at Tanjung Intan Port Cilacap and which is very influential for the smooth process of unloading coal from coal carriers to Tanjung Intan Port, Cilacap. This study aims to determine the factors that affect the ship's docking schedule, pilotage services, loading and unloading productivity on the waiting time of the ship. This research was conducted at Tanjung Intan Port, Cilacap. Data was collected through observation, literature study, interviews, documentation and questionnaires. The analysis technique used is multiple linear regression with the help of SPSS V.26 program. Based on the results of research and multiple analysis, the following equations are generated:Y = 0.254 +0.297X1+0.585X2+0.177X3+µ. Based on empirical facts and the results of multiple linear regression equations, it is shown that the Ship docking schedule variable (X1) has t count (3.409) > t table (1.98373), pilotage service variable (X2) has t count (5.809) > t table (1.98373), and loading and unloading productivity (X3) has t count (2.967) > t table (1.98373). As for the value of the adjuster R2 = 0.582. This means that 58.2% of the dependent variable (Y) can be explained by the independent variables, namely Ship docking schedules, guidance services, and loading and unloading productivity. While the rest (100% - 58.2%) = 41.8% is explained by other reasons outside the variables studied. Thus, the results of the study show that the availability of docks, guidance services, and loading and unloading productivity has a positive and significant effect on waiting time for ships at Tanjung Inttan port, Cilacap.